Survey of Indoor Air Pollution Health Literacy among Community-dwelling Adults in Taiwan - Jia-Ling Wu; Yu-Han Huang; Yi-Chin Huang; Chien-Cheng Jung; Pei-Chen Lee; Ming-Yeng Lin; Wen-Hsuan Hou; Chung-Yi Li (Aerosol and Air Quality Research)
Abstract This study aimed to investigate the level of indoor air pollution health literacy (IAPHL) among adult residents of Taiwan and the associated covariates. A cross-sectional web-based online survey of 647 adults in Taiwan was conducted from May to October 2021 using a reliable and valid IAPHL instrument. We used weighted multiple linear regression models to identify covariates significantly associated with overall and four matric-specific IAPHL scores. The weighted sample size was 616 subjects aged between 20 and 88 years old (mean: 45.8 years, standard deviation: 18.1). Generally, adult residents of Taiwan showed only a moderate level of overall IAPHL, with the highest and lowest matric-specific score for “understanding” and “appraisi ng,” respectively. The key factors associated with adults’ IAPHL included sex, age, work related to indoor air pollution, smoking status, exposure to second-hand smoke, budget for improving indoor air quality, and number of beneficial goods used. The community-dwelling adults in Taiwan had only moderate levels of IAPHL. Adults with certain characteristics associated with low IAPHL should be the objects of further educational interventions or public health policy-making aiming to improve IAPHL. To improve the IAPHL level of adults, we might need to focus on characteristics such as indoor air pollution information provision and health risk perceptions.